THE EFFECT OF FERMENTED PAPAYA LEAF EXTRACT (Carica papaya L.) GIVEN THROUGH DRINKING WATER ON THE INTERNAL ORGANS OF SUPERIOR VILLAGE CHICKEN BALITBANGTAN (KUB) - M.M., Zagoto,; Dewi, I G.A.M.K.; Wibawa, A.A.P.P (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
The objective of this research is to explore the effect of administering fermented papaya leaf extract via drinking water on the health of internal organs in KUB chickens. This study involved 64 KUB chickens that were 10 days old. The research took place over a two-month period in Banjar Dinas Dukuh, located in Demung Village, Kediri District, Tabanan Regency, Bali. The study employs a Completely Randomized Design (RAL) with 4 treatments and 4 replications. The treatments are as follows: P0 (0% papaya leaf extrat), P1 (2% papaya leaf extrac), P2 (4% papaya leaf extract), and P3 (6% papaya leaf extrac). This study examined variables such as the proportions of the heart, liver, gallbladder, spleen, and pancreas. The study found that adding fermented papaya leaf extrat to drinking water had no significant effect (P>0.05) on the percentage of heart, liver, gallbladder, spleen, and pancreas. From these results, we can conclude that using fermented papaya leaf extrat at concentrations of 2%, 4%, and 6% in drinking water does not influence the size of these organs in KUB chickens. So, this extract is considered safe for use in the drinking water of KUB chickens.